Temperature measurement of tribological parts in swash-plate type axial piston pumps - Kazama, Toshiharu (Ventil (Ljubljana), 2011)
Temperatures of a swash plate, cylinder block, and a valve plate of swash-plate type axial piston pumps with a rotating cylinder block and a rotating swash plate were measured. Thermocouples were embedded underneath these parts. Hydraulic mineral oils with ISO VG22, 32, 46, and 68 and a water-glycol type hydraulic fluid with VG32 were used as test fluids. The maximum discharge pressure was 20 MPa and the maximum rotational speed was 28.3 rps. The inlet oil temperatures were specified as 293-313 K. At the atmospheric pressure to the maximum discharge pressure, the temperatures, flow rates, and the torque were measured. Results support the following conclusions: i) as the discharge pressure increased, the temperatures of the swash plate, cylinder block, and the valve plate increased in almost direct relation; ii) the cylinder block temperature at the bottom dead center of the pistons increased markedly; iii) the temperature increases using the water-glycol fluid were noticeably smaller than the rises using the mineral oils; and iv) the temperature rises became large for higher fluid viscosity and lower inlet oil temperature.
Keywords: aksialna batna črpalka; fluidna tehnika; temperatura; tribologija